Pengobatan Tradisional Etnik Batak Toba - Intan Ayu (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Knowledge of the use of traditional medicine in the Toba Batak sub-ethnic has not been widely disclosed. This knowledge is passed down from generation to generation orally and has very limited documentation so it has the potential to be lost. Therefore, this research aims to describe local knowledge about the use of traditional medicine by the Toba Batak sub-ethnic in Sipagabu Village. Data collection methods were carried out using semi-structured interviews and participant observation with informants. The data collected was analyzed using descriptive statistics. In this research, the informants consisted of 51 Toba Batak sub-ethnic people who had knowledge about the use of traditional medicine using 115 medicinal plants used, belonging to 100 genera and 49 families. The main families of medicinal plants used by the Toba Batak sub-ethnic community are Asteraceae, Fabaceae and Zingiberaceae, and Poaceae. Medicinal plants used to cure diseases are grouped into natural diseases, supernatural diseases, uncommon diseases, and certain diseases that are treated using traditional herbs.